O processo de crescimento em Gestalt - terapia: um diálogo com a teoria do amadurecimento de D. W. Winnicott - Poppa, Carla Cristina (2013)
Despite being a widely discussed topic among authors of Gestalt - therapy, the accumulated knowledge about the process of growth is not enough to sustain the clinical reasoning of Gestalt - therapists both children and adults. Thinking of contributing to the process of knowledge construction within this approach, this study aims to describe the gestalt mode of conceiving the growth process and care necessary to meet the needs related to the early period of life. This goal aims to be achieved through the establishment of a dialogue with the theory of maturation of D. W. Winnicott. Therefore, this work presents the philosophical assumptions, key concepts of Gestalt - therapy and child development process from the point of view of this approach. The theory of maturation is also presented as well as the similarities between the two approaches and the distances. The dialogue driven by the theory of maturation identified care that meet the needs of constituent self. The care raised are: satisfaction of needs, confirmation of bodily needs, satisfaction of needs in an affective and consistent way, offering opportunity for the baby to go through their contact cycles in a autonomous way, object or person exercising the paradoxical function, limits and confrontations, host vulnerability, opportunities to repair possible damage. And the needs constitutive of the self, which this study suggests that may be termed as primary or basic needs are: sensory experiences of contact cycles, psychosomatic integration, experience rest accompanied, autonomy to move through contact cycles, opening for play and for interhuman, constitution of the contact boundary, development of the capacity to make creative adjustments, expression of singularity and appropriation of aggression